Dexamethasone-associated metabolic effects in male mice are partially caused by depletion of endogenous corticosterone - Koorneef, Lisa L.; van der Meulen, Merel; Kooijman, Sander; Sánchez-López, Elena; Scheerstra, Jari F.; Voorhoeve, Maaike C.; Ramesh, Ajith N. Nadamuni; Rensen, Patrick C. N.; Giera, Martin; Kroon, Jan; Meijer, Onno C. (Frontiers in Endocrinology, 2022)
Synthetic glucocorticoids are clinically used to treat auto-immune and inflammatory disease. Despite the high efficacy, glucocorticoid treatments causes side effects such as obesity and insulin resistance in many patients. Via their pharmacological target, the glucocorticoid receptor (GR), glucocorticoids suppress endogenous glucocorticoid secretion. Endogenous, but not synthetic, glucocorticoids activate the mineralocorticoid receptor (MR) and side effects of synthetic glucocorticoids may thus not only result from GR hyperactivation but also from MR hypoactivation. Here, we tested the hypothesis that reactivation of MR with corticosterone add-on treatment can attenuate the metabolic effects of the synthetic glucocorticoid dexamethasone. Male 8-week-old C57Bl/6J mice received a high-fat diet supplemented with dexamethasone or vehicle, and were subcutaneously implanted with low-dose corticosterone- or vehicle-containing pellets. Dexamethasone strongly reduced body weight and fat mass gain, while corticosterone add-on partially normalized this. Dexamethasone-induced hyperglycemia and hyperinsulinemia were exacerbated by corticosterone add-on, which was prevented by MR antagonism. In subcutaneous white adipose tissue, corticosterone add-on prevented the dexamethasone-induced expression of intracellular lipolysis genes. In brown adipose tissue, dexamethasone also upregulated gene expression of brown adipose tissue identity markers, lipid transporters and lipolysis enzymes, which was prevented by corticosterone add-on. In conclusion, corticosterone add-on treatment prevents several, while exacerbating other metabolic effects of dexamethasone. While the exact role of MR remains elusive, this study suggests that corticosterone suppression by dexamethasone contributes to its effects in mice.